2017
DOI: 10.1097/mnm.0000000000000687
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid PET/MRI-based delineation of gross tumor volume in head and neck cancer and tumor parameter analysis

Abstract: Delineating GTV on hybrid PET/MRIs is feasible, and aTL, the threshold boundary of BTV, was correlated inversely with the SUVmax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Studies of other tumor locations (e.g., esophagus, lung, pancreas, head and neck) have shown that the additional biological information of PET has an effect on the variation in the GTV during radiation therapy, can reduce the risk of positioning error and in uence the normal tissue dose-volume histogram and the calculation of probability values in corresponding normal tissue [15,16,17]. Ma, J. T. et al [18] showed that GTV contouring based on hybrid PET/MRI for head and neck cancers is feasible and may provide improved accuracy. In their study, GTV VIS and GTV FUS were larger than GTV MRI with the use of hybrid PET/MRI images, which was similar to our ndings, but tumor site determinations were different.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies of other tumor locations (e.g., esophagus, lung, pancreas, head and neck) have shown that the additional biological information of PET has an effect on the variation in the GTV during radiation therapy, can reduce the risk of positioning error and in uence the normal tissue dose-volume histogram and the calculation of probability values in corresponding normal tissue [15,16,17]. Ma, J. T. et al [18] showed that GTV contouring based on hybrid PET/MRI for head and neck cancers is feasible and may provide improved accuracy. In their study, GTV VIS and GTV FUS were larger than GTV MRI with the use of hybrid PET/MRI images, which was similar to our ndings, but tumor site determinations were different.…”
Section: Discussionmentioning
confidence: 99%
“…We consider that this may be related to the imaging limitations of 18 F-FDG PET in liver cancer. Unlike in lung cancer patients, 18 F-FDG PET has already been established to play a role in the application of target volume contouring [21]. In addition, the artifacts caused by tumor location, anatomical boundaries, clinical situations, and patient cooperation during examination have a great impact on the quality of the contouring [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations